Pharmacological effects and mechanisms of medicine food homology species and active ingredients in ameliorating ovarian aging - Chen, Jiayi; Li, Xiaotian; Lai, Xinle; Xu, Ruoyi; Liu, Zheqi; Xing, Jia; Yang, Liuqing; Zhang, Qin (Frontiers in Nutrition, 2026)
Ovarian aging is the process of decline in ovarian reserve, endocrine function with age, leading to reduced fertility and increased risk of various related diseases. In recent years, medicine food homology (MFH) species have attracted much attention for their potential to delay ovarian aging due to their dietary and medicinal values. In this review, we have focused on the intervention of MFH species and active ingredients on ovarian aging, with an emphasis on the molecular mechanisms involved in antioxidant, anti-inflammatory, apoptosis inhibitory, balance of autophagy, maintenance of genome stability, mitochondrial function protective and estrogen-like effects through multiple signaling pathways (e.g., PI3K/Akt, Nrf2/HO-1, SIRT1/mTOR, Nrf2/ARE, etc.). Possessing the characteristics of multi-pathway and multi-target effects, MFH species and active ingredients provide new ideas for the research and development of health food and functional preparations. High-quality clinical studies are still needed for verification.